Analisis Pengaruh Struktur Modal dan Tata Kelola Perusahaan Terhadap Kinerja Keuangan Perbankan Syariah Besar di Indonesia - Mila Salbiyah; Pina Aulia Maharani; Wahidah Nazmi Lailia; Alfiana Alfiana (Indo Publishing, 2026)
This study aims to analyze the effect of Capital Structure, measured by Debt Equity Ratio (DER), and Corporate Governance, measured by Independent Board of Commissioners (DKI), on Financial Performance, measured by Return on Assets (ROA), in the five largest Islamic banks in Indonesia (BSI, Bank Mega Syariah, Bank Aceh Syariah, Bank Muamalat, and BJB Syariah) during the period 2020-2024. The method used in this study is panel data analysis with a quantitative approach. The data used was taken from the annual financial reports and sustainability reports of each bank. The results of the study show that, overall, DER and DKI have a significant impact on ROA. However, when viewed individually, DER does not have a significant impact, while DKI has a positive and significant effect on ROA. These findings indicate that good corporate governance is an important factor in improving the financial performance of Islamic banks in Indonesia.